Em casa, na pista ou na escola é tanto babado: espaços de sociabilidade de jovens travestis - Monzeli, Gustavo Artur (Universidade Federal de São Carlos, 2013)
The aim of this study was to understand, from the experience of four young people who at some point in research called themselves transvestites , residing in São Carlos (SP), the main techniques and strategies used by them for the management and manipulation of their own characteristics regarding their body, subjectivity and identity, in order to participate in certain spaces of sociability, focusing on family contexts, formal education institutions and also prostitution. The work has been organized into four sections. Initially, it introduces an historical debate and academic production about the topic related to gender and sexuality, then it addresses entrance to the search field, from ethnographic contributions and, finally, to contextualize the territories where the research took place. The second section considers the multiplicity of ways to consider and to construct signs of what is considered feminine in bodies assigned as male. Additionally, it presents the history of each interlocutor of this research, trying to point out their unique experiences in these body, subjective and identity building processes. In the third section, we discuss the different techniques and strategies used by them to participate in different contexts such as family, school and prostitution, and how these relations are built depending on the persons involved, as well as their interests and desires. And lastly, contextualizes the propositions of social occupational therapy and its possible implications in everyday life of the individuals in their territories belonging, pointing out how the circulation of these young people in their territories have repercussions on the levels of insertion and restriction, allowing or not their existences in different spaces. It is believed that this dissertation contributes, beyond the multiplicity of forms of construction and understanding bodies, subjectivities and transvestites identities, with a dialogue among the possible links between social occupational therapy and circulation of individuals in their territories belonging.
Keywords: Terapia ocupacional; Travestilidade; Terapia ocupacional social; Corpo; Montagem corporal; Travestility; Social occupational therapy; Body; Montage / dismontage of the bodies; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL